1983
DOI: 10.7164/antibiotics.36.1651
|View full text |Cite
|
Sign up to set email alerts
|

The myxopyronins, new inhibitors of bacterial RNA synthesis from Myxococcus fulvus (Myxobacterales).

Abstract: From the culture supernatant of the myxobacterium, Myxococcus fulvus strain Mx f50, an antibiotic activity was isolated which blocked growth of many Gram-positive and several Gramnegative bacteria, but not of yeasts and fungi. The activity consisted of two closely related compounds, myxopyronins A and B. The myxopyronins appear to be new antibiotics, and seem to specifically inhibit bacterial RNA polymerase.In this article, we present data on a new antibacterial compound, myxopyronin ( Fig. 1)1), which was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 10 publications
4
83
0
3
Order By: Relevance
“…2) were isolated from cultures of Myxococcus fulvus and displayed broad-spectrum antibacterial activity against Gram-positive and -negative bacteria by inhibiting transcription initiation (133,134). Mechanistic studies showed that myxopyronins bind to the switch region and lock the clamp and switch regions in a partly closed/fully closed conformation.…”
Section: Myxopyronin Corallopyronin Ripostatin and Squaramidesmentioning
confidence: 99%
See 1 more Smart Citation
“…2) were isolated from cultures of Myxococcus fulvus and displayed broad-spectrum antibacterial activity against Gram-positive and -negative bacteria by inhibiting transcription initiation (133,134). Mechanistic studies showed that myxopyronins bind to the switch region and lock the clamp and switch regions in a partly closed/fully closed conformation.…”
Section: Myxopyronin Corallopyronin Ripostatin and Squaramidesmentioning
confidence: 99%
“…Although the switch region is conserved across prokaryotic and eukaryotic RNAPs, the adjacent segments are conserved only in bacterial RNAPs, which may explain the specificity of myxopyronins against bacteria (132,133). It was shown that ␤ E1272, E1279, and S1322 and ␤= G344, K345, and K1348 were involved in polar interactions with both myxopyronin A and 8-desmethyl myxopyronin B. Mutagenesis studies demonstrated that amino acid substitutions at ␤ residues E1279 and S1322 and ␤= residue K345 generated resistance against 8-desmethyl myxopyronin B, while changes at ␤ V1275 and L1291 and ␤= K345 resulted in resistance to myxopyronin A (132,135).…”
Section: Myxopyronin Corallopyronin Ripostatin and Squaramidesmentioning
confidence: 99%
“…fulvus HR4, DSM 2549), respectively. (Irschik,1985;198378) Their common structural motive is a 4-hydroxy--pyrone ring with two side chains attached at C3 and C6 positions. A crystal structure of RNA-polymerase-myxopyronin complex was obtained by Ebright and co-workers identified the "switch region"…”
Section: Virginiamycin Mmentioning
confidence: 99%
“…The resistance rate for Myx is 4 ؋ 10 ؊8 to 7 ؋ 10 ؊8 per generation, which is equal within error to the resistance rate for Rif (3 ؋ 10 ؊8 to 10 ؋ 10 ؊8 per generation). Substitutions conferring Myx resistance were obtained in the RNAP ␤ subunit [six substitutions: V1080(1275)I, V1080(1275)L, E1084(1279)K, D1101(1296)E, S1127(1322)L, and S1127 (1322) Mf50 (18,20,23,49). Myx exhibits broad-spectrum antibacterial activity, with potent antibacterial activity against most Gram-positive species and some Gram-negative species.…”
mentioning
confidence: 99%